Testicular yolk sac tumor and impaired spermatogenesis in a Holstein Friesian calf. (3rd September 2015) - Schindewolffs, Lia; Dierks, Claudia; Heppelmann, Maike; Gähle, Marion; Piechotta, Marion; Beineke, Andreas; Brehm, Ralph; Distl, Ottmar
Abstract: Yolk sac tumors are testicular germ-cell tumors of the non-seminoma type. In cattle, this neoplasm is very rare and to date has only been described three times. In human males, it usually occurs in infants and children. Immunohistochemistry provides solid criteria for diagnostics. Especially present pathognomonic Schiller–Duval bodies are helpful for identification. In this report, a 32-day-old Holstein Friesian calf presented with a highly enlarged right testis. Sonographic examination was performed and blood samples were taken to measure testosterone and estrogen levels. Furthermore, the testis was surgically removed and macroscopically, histologically, and immunohistochemically examined which lead to the diagnosis of testicular yolk sac tumor. The second testis was descended until the age of nine months and histology revealed impaired spermatogenesis. This report provides the first sonographic images of bovine testicular yolk sac tumor as well as the first information about hormone levels in calves with this neoplasm. It also shows the importance to combine anamnesis, histomorphological, and immunohistochemical findings in order to diagnose yolk sac tumors when pathognomonic structures are not present.